Disgust propensity, fear of contamination and underlying dimensions of obsessive-compulsive symptoms - Petra Sif Markkusdottir Lappalainen 1989- (2012)
An exploratory study was conducted to investigate the mediating role of harm avoidance and incompleteness, the proposed underlying motivational factors of obsessive-compulsive disorder (OCD), in the relationship between disgust and fear of contamination. In total, 170 undergratuate students at the University of Iceland answered questionnaires and data from 148 participants was analysed using linear regression. The mediating effects of harm avoidance and incompleteness was tested using three different self-report measures, a measure of these two underlying motivational dimensions (OC-TCDQ) and a measure of symptoms of not-just-right experiences (NJRE-Q-R) and beliefs related to overestimation of threat and responsibility (OBQ-44). Results showed that disgust was associated with fear of contamination and that neither harm avoidance (OC-TCDQ) nor overestimation of threat (OBQ-44) significantly mediated the relationship between disgust and fear of contamination. However, incompleteness and the number of not-just-right experiences (NJRE-Q-R) were significant mediators. This indicates that contamination-related OCD symptoms may be more emotion or sensation-based rather than a result of cognitive distortions in people whose contamination symptoms are related to the emotion of disgust. Such patients may engage in compulsions when feeling disgusted not because they need to avoid possible future harm but rather because they cannot get rid of feelings of incompleteness if they do not perform their compulsions.